ANALYSIS ON THE MUDHARABAH CALCULATION OF IMPROVEMENT REVENUE TRADERS IN BMT BENING ATI GROBOGAN DISTRICT - Tida, Khusnamah (Accounting, 2010)
The existence of an existing conventional bank interest rate system put in operation, while the Islamic Bank are not familiar with the term of interest but is a term used for the results. Banking with profit-sharing system designed by involved unity in the risks and share the results of operations between the owner of the funds that keep their money in the bank, with banks and fund managers as well as people who need funds that can be status as a borrower or a fund manager.With financing coupled with capital management and business guidance to help increase business productivity, which in turn will affect the increased income of small traders. This is the basis for the author to take the title